The Ratio of Second to Fourth Digit Length (2D:4D) and Heart Disease (Bangladesh Journal of Medical Science, 2016)
Objectives: The risk of getting heart diseases is unpredictable due to many predisposing factors range from lifestyle to genetic inheritance. Scientist made the discovery after studying men of various age who had suffered heart disease made a finding; the length of ring fingers (4D) are shorter than index fingers (2D) are at greater risk of premature heart attack at their early 30. Based on these facts, we carried out this project work by analyzing 2D and 4D ratios with the perspective of risk of heart disease among the Malaysian undergraduate students.Materials and method: A cross sectional study using questionnaire about subjects family history of heart related problems if any, followed by measurement of length of second and fourth digit was carried out. 2D:4D ratio index was calculated. Data obtained were tabulated according to index more than 1 and less than 1.Results and discussion: In the present study, total 66 subjects (n= 120) presented with a ratio greater than 1.0, this accounted for a total of 55%, while remaining 45% of subjects had 2D:4D